Monte Carlo analysis of the influence of germanium dead layer thickness on the HPGe gamma detector experimental efficiency measured by use of extended sources. (January 2015) - Chham, E.; García, F. Piñero; El Bardouni, T.; Ferro-García, M. Angeles; Azahra, M.; Benaalilou, K.; Krikiz, M.; Elyaakoubi, H.; El Bakkali, J.; Kaddour, M.
Abstract: We have carried out a study to figure out the influence of crystal inactive-layer thickness on gamma spectra measured by an HPGe detector. The thickness of this dead layer (DL) is not known (no information about it was delivered by the manufacturer) due to the existence of a transition zone where photons are increasingly absorbed. To perform this analyses a virtual model of a Canberra HPGe detector was produced with the aid of MCNPX 2.7 code. The main objective of this work is to produce an optimal modeling for our GPGe detector. To this end, the study included the analysis of the total inactive germanium layer thickness and the active volume that are needed in order to obtain the smallest discrepancy between calculated and experimental efficiencies. Calculations and measurements were performed for all of the radionuclides included in a standard calibration gamma cocktail solution. Different geometry sources were used: a Marinelli and two other new sources represented as S(1) and S(2). The former was used for the determination of the active volume, whereas the two latter were used for the determination of the face and lateral DL, respectively. The model was validated by comparing calculated and experimental full energy peak efficiencies in the 50–1900 keV energy range. the results show that the insertion of the DL parameter in the modeling is absolutely essential to reproduce the experimental results, and that the thickness of this DL varies from one position to the other on the detector surface. Highlights: Modeling of a HpGe detector was realized with the manufacture's data. Inclusion of dead layer has improved the simulation of the experimental efficiencies. Dead layer and volume of crystal are the parameters most influent on calculations. Lower energies are more sensitive to the change in the dead layer thickness. Variation of the active volume has a clear effect on the higher energies.